Introduction: Film Studies and Analytic Aesthetics in Dialogue. Issue 3 (1st December 2020) - Slugan, Mario; Terrone, Enrico
Abstract : Since the 1970s with Stanley Cavell's work, and later with contributions such as those by Noël Carroll, George Wilson, Gregory Currie, and Berys Gaut, film has become a respectable object of philosophizing among Anglo-Saxon philosophers. Still, when it comes to the relationship between film and philosophy, the focus is mostly on how philosophy can help better understand film with little or nothing on how film studies can contribute to philosophical aesthetics. This special issue is aimed at encouraging a more balanced interaction between analytic aesthetics and film studies.